O Museu dos Militares Mineiros e a valorização da memória do sujeito bombeiro militar - Andréa Lomeu Beltrão (2020)
This work aims to enhance the military memory of bombing at the Museum of Military Miners (MMM) through the development of a facility that works with missing fragments of six participants of the Brotherhood of Fire, an association that brings together retired or reserve military firefighters. Founded in March 2014 by the Government of Minas Gerais, through the Secretary of State for Culture (SEC-MG), this cultural equipment is dedicated to the military institutions of Minas Gerais. The collection contained in it was the starting point of the present study in order to promote a dialogue between the installation, the subjects' affective memory objects and the museum institution. Applicable to an interdisciplinary approach involving historical, epistemic and affective aspects, to draw up an interview protocol for the six retired or retired military firefighters, mobilizing memories and respecting the firefighter's craft. Through a narrative chart, these interviews were analyzed and fragmented into an auditory material that supported a proposed installation. The fragments were selected by the emergence of meanings attributed to the themes related to the body, work artifacts, family and remarkable career facts. The product of this investigation is the installation planning that can be incorporated into the MMM collection in an expography revision context.